HUBUNGAN KEAKTIFAN ORGANISASI SISWA INTRA SEKOLAH DAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM PADA SISWA SMPIT WIDYA CENDIKIA - Munawaroh, Munawaroh; Sudrajat, Sanin (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
To drive active OSIS activities, national educational leadership is needed, namely leadership that requires a stable system, adequate funding, professional human resources and has the following requirements or characteristics: Devotion to God Almighty, high intelligence, have a strong physique, broad knowledge, self-confidence, can be a member of a group, fair and wise, firm and take the initiative, have the capacity to make decisions, have emotional stability, be physically and spiritually healthy. Based on the conditions that must be met to become an OSIS leader or administrator, it turns out that it is not easy, apart from having the will, ability and knowledge, apart from that you also have to be able to manage your time as well as possible so that lessons are not disturbed and go through several selections. OSIS as the only student organization in the school, is a means of organizational training and a forum for activities for students at school, so it can be concluded that the progress and development of school activities is very dependent on the OSIS work program, leadership attitudes and basic knowledge regarding good organizational management and activities. OSIS administrators who are guided by OSIS supervisors. Seeing this important role and position, the OSIS needs to be managed as well as possible. Organizations in general can be interpreted as providing a structure or arrangement, namely in arranging/placing people in a cooperative group, with the aim of placing relationships between people in terms of their respective obligations, rights and responsibilities, determining the structure, relationship of duties and responsibilities. It is intended to organize an activity to lead to a common goal. Discipline is an action carried out in accordance with applicable regulations or doing something in accordance with applicable norms. Learning outcomes are sentences consisting of two words, namely, "results" and "learning" which have different meanings. This research was carried out at SMPIT Widya Cendikia Serang. The research object is students at SMPIT. This research uses a survey method with primary data collection